PENGARUH MEDIA VLOG DENGAN MODEL ARIAS (ASSURANCE, RELEVANCE, INTEREST, ASSESSMENT, SATISFACTION) TERHADAP KETERAMPILAN KOMUNIKASI VERBAL SISWA DALAM PEMBELAJARAN IPS - Siska Nurdianty, - (2020)
The Influence of Vlog with the ARIAS (Assurance, Relevance, Interest, Assessment, Satisfaction) Model on Students Verbal Communication Skill in Social Studies Learning ABSTRACT One dimension of social studies learning is the skill dimension, which includes communication skills. This research focuses on verbal communication in which the delivery of messages through writing and orally. The purpose of this study was to examine and see the effectiveness of the vlog media with the ARIAS model on verbal communication skills of students at SMP Muhammadiyah 6 Bandung. The research method uses a pre-experimental method with the one-group pretest-posttest design. The sample of this study is students of class VIII-A SMP Muhammadiyah 6 Bandung. The instrument used in this study was a test. After the data is collected then it is processed using a hypothesis test or t test using the SPSS v20 application. Obtained the analysis results there are changes in students' verbal communication skills between before and after using vlog media treatment with the ARIAS model. Differences in students' verbal communication skills are based on hypothesis testing, the significant value (sig 2-tailed) is 0,000 < 0.05, so H1 is accepted or H0 is rejected and the hypothesis is accepted. So it can be concluded that the vlog media with ARIAS model in social studies learning is effective for improving verbal communication skills of students of class VIII-A of SMP Muhammadiyah 6 Bandung. Keywords: Vlog Media, Verbal Communication, Social Studies Learning.